2019
DOI: 10.1242/jeb.200832
|View full text |Cite
|
Sign up to set email alerts
|

Mixing it up: the biological significance of hybrid skeletal muscle fibers

Abstract: Skeletal muscle fibers are classified according to the myosin heavy chain (MHC) isoforms and other myofibrillar proteins expressed within these cells. In addition to ‘pure’ fibers expressing single MHC isoforms, many fibers are ‘hybrids’ that co-express two or more different isoforms of MHC or other myofibrillar proteins. Although hybrid fibers have been recognized by muscle biologists for more than three decades, uncertainty persists about their prevalence in normal muscles, their role in fiber-type transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 190 publications
(250 reference statements)
2
32
0
Order By: Relevance
“…2015). It has also been demonstrated that the TA may contain hybrid fibres with different myosin heavy chain expression (Medler, 2019). These different contractile structures may have different post‐exercise requirements for energy recovery.…”
Section: Discussionmentioning
confidence: 99%
“…2015). It has also been demonstrated that the TA may contain hybrid fibres with different myosin heavy chain expression (Medler, 2019). These different contractile structures may have different post‐exercise requirements for energy recovery.…”
Section: Discussionmentioning
confidence: 99%
“…These different Myh isoforms are coded by different genes, and in mammals, fast Myh (fMyh) genes, including Myh2, Myh1, Myh4, embryonic Myh3, neonatal Myh8, and extraocular Myh13 are clustered on a single locus while the slow Myh7 gene lies on another locus 16 . Myofibers can express one, two or three MYH isoforms at the same time at protein and mRNA level [17][18][19][20] . Myofibers expressing more than one MYH isoform are called hybrid fibers in contrast to pure fibers expressing only one isoform.…”
mentioning
confidence: 99%
“…The fiber type of the quadriceps femoris muscle is IIx/IIb in rodents and IA/IIA and IIA/IIX in humans, which are commonly referred to as fast-twitch fibers. Most other skeletal muscle in limbs, other than the soleus muscle, have a similar fiber type composition both in humans and other mammals [80]. Finally, the quadricep femoris has often been used to study exercise [80] and the effects of aging [77,81,82] in mouse and humans.…”
Section: Cisd2 and Exercisementioning
confidence: 99%
“…Most other skeletal muscle in limbs, other than the soleus muscle, have a similar fiber type composition both in humans and other mammals [80]. Finally, the quadricep femoris has often been used to study exercise [80] and the effects of aging [77,81,82] in mouse and humans. In agreement with the results on systemic metabolism ( Figure 1B), we found a gender difference in the histology of skeletal muscle, particularly in the Old-Sed mice.…”
Section: Cisd2 and Exercisementioning
confidence: 99%